Determinants of Hybrid Car Purchasing Decisions: The Role of Price, Promotion, and People in Toyota Consumers - Ajeng Restu Gustiyani; Adi Nurmahdi (ARE Publisher, 2026)
Objectives: This study aims to analyze the influence of price, promotion, and people on purchasing decisions of Toyota hybrid cars at PT Astrido Jaya Mobilindo Karawang. The research focuses on understanding the role of key marketing mix elements in shaping consumer purchasing behavior in the hybrid automotive market. Methodology: This research employs a quantitative approach using a survey method. Data were collected through structured questionnaires distributed to 225 Toyota hybrid car consumers. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 3.2.9 to examine the relationships between variables. Findings: The results indicate that price, promotion, and people have a positive and significant effect on purchasing decisions. These findings suggest that competitive pricing, effective promotional strategies, and the quality of human resources play an important role in encouraging consumers to purchase hybrid vehicles. Conclusion: The study concludes that marketing mix elements, particularly price, promotion, and people, are key determinants of purchasing decisions in the hybrid automotive sector. Therefore, automotive companies are encouraged to strengthen their pricing strategies, promotional activities, and service quality to enhance consumer purchasing decisions.